Patients Perceptions of Opioid Use for Chronic Lower Back Pain in Rural Guatemala - Ruan, Tiffany; Puga, Troy Brian; Onwenu, Jason; Amani, Tafadzwa; Tyler, Robert (Journal of Anaesthesia and Pain, 2023)
Background: Chronic lower back pain is a common cause of disability. Opioids, although not first-line treatment, are often prescribed for chronic lower back pain. The purpose of this study is to understand the perceptions of opioids among the rural Guatemalan population for chronic low back pain to best optimize a shared decision-making process in pain management. Methods: Participants were given a survey regarding demographic information, whether they were offered an opioid prescription for chronic lower back pain, and whether they would take the medication if offered. Participants completed the Prescription Opioid Overdose Knowledge Score (Rx-OOKS) questionnaire, to evaluate knowledge of opioid overdose.Result: The survey results showed that 93.3% of participants were never offered an opioid prescription for chronic low back pain by a provider in Guatemala. However, a majority would have taken an opioid if given the opportunity. Scores on the Rx-OOKS revealed a statistically significant lower mean (p< 0.05) than the United States’ study baseline for the knowledge of signs of prescription opioid overdose construct, actions to take in the opioid overdose construct, and total score construct.Conclusion: This research study was able to show that although there is a low prevalence of opioid use in rural Guatemala and decreased knowledge of opioid overdose. Thus, physicians and other healthcare providers must do their due diligence to educate their communities about opioid use, opioid overdose, and naloxone use for a potential overdose. This process is essential in the development of a shared decision-making process for pain management.